Spectrum of intraarticular structures’s changes in patients with hemophilic artropathy by magnetic resonance imaging - V. D. Zavadovskaya; L. M. Ogorodova; T. V. Zhogina; Z. A. Mayevskaya; I. S. Remzantseva; O. Yu. Borodin; I. V. Shakhova (Бюллетень сибирской медицины)
The results of joints's magnetic resonance imaging of 10 patients with severe form of hemophilic artropathy are discussing in this article. The purpose of research was to study the state of soft tissue and bone intraarticulare's structures in present group of patients. The form of bones, condition of an articulate cartilage, the joint’s tendons and ligaments, synovium, presence of an intraarticulate exudate, presence and extent of adjournment haemosiderin, and also signal characteristics of a marrow were estimated.